Holographic Measurement of Surface Topography - Limits and New Options - Häusler, Gerd; Willomitzer, Florian (DGsO-Proceedings 2023, 2023)
There is a plethora of options for optical 3D-metrology. Inspired by the progress of digital holography, we discuss two questions: Can we implement all classical (non-holographic) sensors via digital holography? And even more interesting: Can digital holography enable options beyond classical sensors?
Keywords: holography; metrology; topography; 3-D